PPP in Malaysia : does it provide a fair interest? - Nur Hasimah binti Jaaffar (Management Centre, International Islamic University Malaysia, 2010)
PPP or PFI system is currently widely practice by the Government in delivering public projects for the purpose of public use. This study would determine whether the Malaysian model is based on the United Kingdom Privatisation model or the PPP/PFI model. Besides that, I will examine the features of Malaysia's Privatisation programme with PPP/PFI system and focusing on how the system gives direct impact to all the parties. This study will try to discover whether Malaysia applies Privatisation or PPP system in projects implemented by government. In addition, the study examines the difference and benefits of the various public-private sector programmes that were previously and currently adopted in Malaysia. This study also will analyse whether the implementation of PPP projects in Malaysia is a win-win policy in all three parties; public services, private sector and the society at large. As a conclusion, the study hopes to find out whether the PPP/PFI model has been successful by looking at the Key Performance Indicator (KPI) as a performance measurement systems, and if so, to identify the challenges and obstacles that has affected the performance of the model.